Estimation of genetic parameters of cone and seed characteristics in clonal seed orchard of spheroid Scots pine - Murat ALAN (Turkish Journal of Forestry, 2018)
Spheroid scots pine (Pinus sylvestris L.var. compacta (Tosun) Ü.Akkemik) clonal seed orchard was established with 26 clones in Karabük-Eflani originating Bolu-Çakmaklar in 2004. Three grafts were randomly selected for each clone. 3-24 cones were collected from each graft per clone. Ten characteristics of cones and seeds of the cones have been measured and evaluated. As averages for two years, it was revealed that the yield of seed from the cone was 2 %, the weight of 1000 seeds was 6 g, the number of seeds in a cone was 12.11 and the seed germination percentage was 45.75 %. In the analysis of variance, it was determined that there were high variations in both clones and years, and there was no variation in the clone year interaction. For ten characteristics, the first-time estimations of broad sense heritability, genetic and phenotypic correlation was varied between 0.25-0.61, 0.23-1.05 and 0.00-0.99, respectively. Findings of the study were intended for management conserving ex situ and adapting to the landscape of spheroid clonal Scots pine seed orchards in Karabük-Eflani and Bolu-Mengen.